Exploration of the Role of Innovation and Entrepreneurship Project in the Construction of Campus Aesthetic Education - Cao Haifeng; Ma Xinzheng (Journal of Educational Issues, 2024)
Improving college students’ aesthetic and humanistic quality is the goal of college aesthetic education in the new era. Under the background of innovation and entrepreneurship in China, the aesthetic education in colleges and universities should be rooted in the general environment of practice. The Beijing municipal innovation and entrepreneurship project Vision of Beauty is a case in point to show that the aesthetic project is an effective path in providing an environment for college students to get involved and experience aesthetic education, and it helps to improve the students’ comprehensive aesthetic quality, promote the construction of campus ecological culture and the effective development of aesthetic education in colleges and universities.